Hymenolepis nana in a renal transplant recipient : to treat or not to treat? - Amin Nordin, Syafinaz; Awang Hamat, Rukman; Osman, Malina; Masri, Siti Norbaya; Mohd Taib, Niazlin; Jamal, Farida Fatema @ Farida (Malaysian Medical Association, 2011)
A case of hymenolepiasis in a renal transplant recipient. Issues discussed include the benefit of anti-parasitic agents as well as the preventive measures.